CORAK MAZHAB PADA FATWA DEWAN SYARIAH NASIONAL MAJELIS ULAMA INDONESIA (Analisis Tentang Mudharabah, Musyarakah Dan Murabahah) - Ahmad Qorib , Ardiansyah, Acme Admira Arafah, (UIN SU, 2018)
There are different types of mazhab adopted in the Fatwa of DSN-MUI related to musharaka, mudaraba and murabaha,. In the fatwa of the DSN-MUI on Musharaka, both in terms material content and applicative,Â if examined substantially, it tends more to Hanafiâs madhhab. However, DSN-MUI fatwas about Mudharabah were different, the DSN-MUI fatwa is mostly to take and agreed on legal basis Syafii as its fatwa. While the DSN-MUI fatwa on Murabaha, the legal basis and the determination substance of the fatwa material, more relies on the same proportion as the four madhhab known so far.Â Thus, in giving the DSN fatwa to be implemented in Indonesia, the Indonesian Council of Ulamaâs had to refer to the various madhhab. Although there are several provisions that are adapted to the conditions of the times, still fatwas do not violate the general rules that have been submitted by the first madhhab.